Analysis of Agricultural Performance of BRICS Countries and Türkiye with CRITIC-Based Grey Relational Analysis Method - Mahmut Masca; Ahmet İnkaya (Ekonomi, Politika & Finans Araştırmaları Dergisi, 2025)
The purpose of this study is to use the CRITIC (Criteria Importance Through Intercriteria Correlation) and GRA (Grey Relational Analysis) approaches to assess the agricultural performance of the BRICS countries (Brazil, Russia, India, China, and South Africa) and Türkiye. The following criteria are applied in order to assess each country's agricultural performance: Livestock Production, Primary (Ton/Population), Crops Production, Primary (Ton/Population), Gross Production Value (constant 2014-2016 thousand US$) (Value/Hectare), Agriculture Self-sufficiency (Export/Import) (%), Agriculture Methane (CH4) Emission from Agriculture (Value/Agricultural Land) in million metric tonnes of carbon dioxide equivalents (Mt CO2e), Agriculture Employment (as a percentage of total employment), and Fertilizer consumption (kilograms per hectare of arable land), Arable land (% of land area). The years 2000, 2010, and 2022 are all included in the analysis. According to the GRA approach, South Africa had the worst agricultural performance in all reviewed years. While Russia had the highest rank in 2000, Brazil rose to the top ten years later, in 2010, its rank remained unchanged in 2022. Specifically, the top and bottom-ranked nations remain unchanged from 2010 to 2022. In terms of Türkiye, it ranked fourth in all studied years.